2023
DOI: 10.1128/spectrum.03957-22
|View full text |Cite
|
Sign up to set email alerts
|

AoSte12 Is Required for Mycelial Development, Conidiation, Trap Morphogenesis, and Secondary Metabolism by Regulating Hyphal Fusion in Nematode-Trapping Fungus Arthrobotrys oligospora

Abstract: Nematode-trapping (NT) fungi are an important natural enemy of nematodes and can capture their prey by producing traps. Hyphal anastomosis and fusion are important for mycelial growth and the colony morphological development of filamentous fungi and are also crucial for the trap morphogenesis of NT fungi. Arthrobotrys oligospora can form complex three-dimensional networks (traps) when sensing the presence of nematodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The most conflict-rich nodes in this study also coincide with the differentiation nodes of NTF nematode traps, which also implies that these genes undergoing ILS may be associated with morphological innovation in NTF. Here, we found that some ILS genes underwent positive selection, especially genes involved in cell membrane system have been shown to be involved in trap morphogenesis (Bai et al, 2023; Chen et al, 2022) and inflation of the constricting ring (Chen et al, 2023). The role of positive selection in the adaptive radiation of cichlids, wild tomatoes, and Jaltomata has also been demonstrated, even though there are gene tree discordances in their evolutionary process (Brawand et al 2014; Pease et al 2016; Wu et al 2018).…”
Section: Discussionmentioning
confidence: 95%
“…The most conflict-rich nodes in this study also coincide with the differentiation nodes of NTF nematode traps, which also implies that these genes undergoing ILS may be associated with morphological innovation in NTF. Here, we found that some ILS genes underwent positive selection, especially genes involved in cell membrane system have been shown to be involved in trap morphogenesis (Bai et al, 2023; Chen et al, 2022) and inflation of the constricting ring (Chen et al, 2023). The role of positive selection in the adaptive radiation of cichlids, wild tomatoes, and Jaltomata has also been demonstrated, even though there are gene tree discordances in their evolutionary process (Brawand et al 2014; Pease et al 2016; Wu et al 2018).…”
Section: Discussionmentioning
confidence: 95%
“…In A. oligospora , Bck1, Mkk1, and Slt2 signaling cascade has been proved to be involved in multi-stress tolerance ( Zhen et al, 2018 ; Xie et al, 2021 ). In addition, some transcription factors downstream of MAPK cascades have been confirmed to be involved in stress resistance, such as Ste12 ( Bai et al, 2023a ), RlmA ( Yang et al, 2023 ), and Swi6 ( Xie et al, 2022 ). Therefore, AoPaks and AoRho-GAPs may influence the stress response by regulating the downstream effectors, including the MAPK cascades and related transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…The trap formation of A. oligospora initially involves annular structures, of which multiple are gradually formed and combine to form a three-dimensional adhesive network; the combination of these annular structures is closely linked to their mycelial fusion with each other [ 50 ]. Recently, we observed that the transcription factor Ste12 is required for mycelial fusion in A. oligospora , and that Fus3-MAPK and five other proteins (Mdr1, Mae1, Vps18, Ubx5, and UDP-glycosyltransferase) could interact with Ste12 [ 51 ]. In this study, the deletion of Aomdr1 caused a reduction in mycelial fusion under nutrient-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The nematode predation efficiencies of the ∆ Aomdr1 mutants showed no obvious changes, suggesting that trapping nematodes requires the involvement of not only traps but also sticky substances on the surfaces of the traps, as well as extracellular proteases. Disruption of Aoste12 has caused a significant increase in numbers of mycelial loops in traps, but has decreased numbers of traps [ 51 ]. The absence of AoMae1, another protein that interacts with AoSte12, has led to increases in the numbers of traps and the numbers of mycelial loops [ 33 ].…”
Section: Discussionmentioning
confidence: 99%